Kedudukan Hak Milik Perorangan Atas Tanah Adat Suku Moi Di Papua Barat (Studi Kasus Pada Kota Sorong Provinsi Papua Barat) - Muhammad Taufiq Hidayat; Eko Rial Nugroho (Fakultas Hukum Universitas Islam Indonesia, 2024)
This abstract discusses the position of individual property rights over the customary lands of the Moi Tribe in the West Papua region using an empirical research approach. The main objective of this research is to analyze how individual property rights to the customary lands of the Moi Tribe are recognized, implemented, and perceived in daily practice, as well as their impact on cultural and environmental sustainability. This study uses empirical research methods. Secondary data was obtained through a study of literature and official documents related to customary land laws and policies in West Papua. The results of the study show that the position of individual property rights over customary land of the Moi tribe faces complex dynamics between customary traditions and formal law. Formal legal recognition of individual property rights over customary land provides legal protection, but sometimes it also has the potential to create internal conflicts within indigenous peoples. Positive impacts are seen in economic empowerment and strengthening of the cultural identity of the Moi Tribe, but challenges such as intergenerational conflicts and development pressures also surface. This research concludes that the harmonious integration between customary law and formal law as well as the active participation of the Moi Tribe community in the management of customary lands is the key to ensuring the protection of sustainable individual property rights and cultural continuity. More inclusive and sustainable policy decisions need to be considered to address these challenges.